Proceedings of the Geologists' Association - Proceedings of the Geologists' Association (Elsevier, 2026)
The Proceedings of the Geologists' Association is an international geoscience journal that was founded in 1859 and publishes research and review papers on all aspects of Earth Science.
FI 0.6
Q3
Keywords: Earth; Space & Environmental Sciences; Geology & Geophysics; Geología; Geofísica; Acuerdos transformativos; Transformative agreements; Ciencias de la Tierra; Geoconservación; Gestión de la Tierra